LITERASI MEDIA KHALAYAK DI ERA KEBERLIMPAHAN INFOMASI DI MEDIA MASSA - Thadi, Robeet (JURNAL ILMIAH SYI'AR, 2019)
The era of information abundance problems has shifted, from the difficulty offinding information to the difficulty of filtering information. This paper aims toexplain the urgency of public media literacy in the midst of the abundance ofinformation presented by the mass media. Media literacy is a concept about theways people question what is watched, observed, read and produced from themedia. Media literacy is needed so that the public as a media audience has theauthority to actively sort out and choose media shows, so that if there is apresentation that only emphasizes sensation, the public can reject it. by notwatching it or switching to other shows. The public can control the contents ofthe media critically and intelligently so that they can detect propaganda, certaininterests or bias in the appearance of the media.